Testing Darwin's transoceanic dispersal hypothesis for the inland nettle family (Urticaceae) - Zeng‐Yuan Wu; Jie Liu; Jim Provan; Hong Wang; Chia‐Jui Chen; Marc W. Cadotte; Ya‐Huang Luo; Bruno S. Amorim; De‐Zhu Li; Richard I. Milne (Ecology Letters, 2018)
Dispersal is a fundamental ecological process, yet demonstrating the occurrence and importance of long‐distance dispersal ( LDD ) remains difficult, having rarely been examined for widespread, non‐coastal plants. To address this issue, we integrated phylogenetic, molecular dating, biogeographical, ecological, seed biology and oceanographic data for the inland Urticaceae. We found that Urticaceae originated in Eurasia c . 69 Ma, followed by ≥ 92 LDD events between landmasses. Under experimental conditions, seeds of many Urticaceae floated for > 220 days, and remained viable after 10 months in seawater, long enough for most detected LDD events, according to oceanographic current modelling. Ecological traits analyses indicated that preferences for disturbed habitats might facilitate LDD . Nearly half of all LDD events involved dioecious taxa, so population establishment in dioecious Urticaceae requires multiple seeds, or occasional selfing. Our work shows that seawater LDD played an important role in shaping the geographical distributions of Urticaceae, providing empirical evidence for Darwin's transoceanic dispersal hypothesis.